Stimulating Critical Literacy through Extensive Reading: A Qualitative Study in an EFL Classroom at Universitas Bina Sarana Informatika - Istihayyu Buansari; Maulani Pangestu; Fiza Asri Fauziah Habibah (Wanastra: Jurnal Bahasa dan Sastra, 2026)
In many EFL classrooms, reading instruction still focuses heavily on linguistic comprehension, often leaving little room for students to question texts or reflect on the social values found in them. As a result, students may understand what a text says but rarely explore what it means beyond the surface. This study aims to explore how Extensive Reading (ER), implemented as an additional reading activity, can support the development of students’ critical literacy. Using a descriptive qualitative design, the research was conducted in an English Prose Analysis class with 38 students at the Faculty of English Literature, Universitas Bina Sarana Informatika. Data were collected through questionnaires and follow-up in-depth interviews. Although all students completed the questionnaire, three volunteered to participate in the interviews, and their insights served as the primary data for deeper analysis. The data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings show that when ER is combined with critical questioning, it encourages students to challenge assumptions, relate texts to broader social and global issues, and develop greater awareness of perspectives such as gender, environmental concerns, and human rights. These results suggest that ER can go beyond improving reading fluency and serve as a meaningful strategy for fostering critical literacy in EFL classrooms. This study adds to the existing discussion on extensive reading by showing how ER activities can also encourage the development of students’ critical literacy in an EFL classroom, a perspective that has not been widely explored in previous studies. The findings also suggest that incorporating critical questions into extensive reading activities can help lecturers guide students to read more reflectively and connect texts with broader social issues.